If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 54 = (x + 10)(2x + -3) Reorder the terms: 54 = (10 + x)(2x + -3) Reorder the terms: 54 = (10 + x)(-3 + 2x) Multiply (10 + x) * (-3 + 2x) 54 = (10(-3 + 2x) + x(-3 + 2x)) 54 = ((-3 * 10 + 2x * 10) + x(-3 + 2x)) 54 = ((-30 + 20x) + x(-3 + 2x)) 54 = (-30 + 20x + (-3 * x + 2x * x)) 54 = (-30 + 20x + (-3x + 2x2)) Combine like terms: 20x + -3x = 17x 54 = (-30 + 17x + 2x2) Solving 54 = -30 + 17x + 2x2 Solving for variable 'x'. Combine like terms: 54 + 30 = 84 84 + -17x + -2x2 = -30 + 17x + 2x2 + 30 + -17x + -2x2 Reorder the terms: 84 + -17x + -2x2 = -30 + 30 + 17x + -17x + 2x2 + -2x2 Combine like terms: -30 + 30 = 0 84 + -17x + -2x2 = 0 + 17x + -17x + 2x2 + -2x2 84 + -17x + -2x2 = 17x + -17x + 2x2 + -2x2 Combine like terms: 17x + -17x = 0 84 + -17x + -2x2 = 0 + 2x2 + -2x2 84 + -17x + -2x2 = 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 84 + -17x + -2x2 = 0 Factor a trinomial. (7 + -2x)(12 + x) = 0Subproblem 1
Set the factor '(7 + -2x)' equal to zero and attempt to solve: Simplifying 7 + -2x = 0 Solving 7 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 0 + -7 -2x = 0 + -7 Combine like terms: 0 + -7 = -7 -2x = -7 Divide each side by '-2'. x = 3.5 Simplifying x = 3.5Subproblem 2
Set the factor '(12 + x)' equal to zero and attempt to solve: Simplifying 12 + x = 0 Solving 12 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + x = 0 + -12 x = 0 + -12 Combine like terms: 0 + -12 = -12 x = -12 Simplifying x = -12Solution
x = {3.5, -12}
| 4(3x+4)+1=7 | | 3x^3+12x^2y^2-96xy^3= | | (16x+4)-36=0 | | -5t^2-20t+96=0 | | -7x+1=-x+1 | | (16x+4)=36 | | 60+1.6Y=176 | | 11+12m+m^2= | | X(2-x)+b(2-b)=5 | | 2x^2+17x-84=0 | | 9x=4-7x | | x^2+29x+17= | | 7q^2-2pq-7q+2p= | | X=110+-1Y | | 1.6X+1.6Y=176 | | (X+15)+x+39=180 | | y(x-8)-5(x-8)= | | 2x+2b=5 | | -32xy-98x^2= | | 2(3b^2+2)+4b-5= | | 6x^2+12x-48= | | 12p^2=8-10p | | R*1.6(R+10)*1.6=176 | | 2(2x+3)=2x-12 | | 2x-4(x-2)=2x+4 | | 12m^2+37m-10=0 | | (3x-18)+2x+x=180 | | 60r-50=15r | | x^2-11=4x | | 2m^2+6m+1m+6=0 | | 6.28=3.14x | | 4x-20+30=2x |